2020
DOI: 10.1139/cjas-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent lighting program does not hinder the performance of broiler chickens and promotes energy economy

Abstract: The objective of this study was to evaluate the performance of broiler chickens in different lighting programs. Broiler chickens were fed on feeders of different colours at different breeding phases. In total, 240 Cobb500™ chicks mixed at 1 d of age were used. They were distributed in a completely randomized design. The treatments followed a 2 × 4 factorial design: two lighting programs (continuous and intermittent), and four colours of feeders (white, green, blue, and red). The birds were evaluated for weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…Photoperiod can impact broiler performances from embryo phase to marketing time [29] . Previous studies usually compare the differences in production performance and physiology of broilers under different light regimes to select an appropriate photoperiod [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Photoperiod can impact broiler performances from embryo phase to marketing time [29] . Previous studies usually compare the differences in production performance and physiology of broilers under different light regimes to select an appropriate photoperiod [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Calik et al reported nearly 2,500 g of Cobb500 broilers' BW in control and treatment groups on the 42nd day of their experiment ( 50 ). The mean weight gain of Cobb500 broilers on the 42nd day of the Manfio et al study was 2,828.6–2,806.9 g depending on the experiment condition ( 51 ). Castro et al reported BW values in the negative control group on the 42nd day that are similar to our data (2,082 g).…”
Section: Discussionmentioning
confidence: 99%
“…It aims to maximize broiler growth by increasing feed consumption (Soliman and Hassan, 2019). Recent research (Hassanzadeh et al, 2012;Manfio et al, 2019) has shown that short-day length (intermittent lighting) saves energy and improves broiler welfare.…”
Section: Light Durationmentioning
confidence: 99%